Rediscovery and redescription of Laelaps lignicola G. & R. Canestrini, a remarkable myrmecophilous mite of the genus Cosmolaelaps Berlese (Acari: Mesostigmata: Laelapidae) from Italy - Plumari, Massimo; Joharchi, Omid (Zootaxa, 2017)
Laelaps lignicola G. & R. Canestrini, 1882 is redescribed on the basis of numerous adults and deutonymphs, collected from Italy more than a century after its description. Despite its setiform setae without a discernible asymmetric swelling, this species fits the current concept of the genus Cosmolaelaps Berlese for all remaining diagnostic characters. Males of L. lignicola and Cosmolaelaps vacuus (Michael) share the presence of a basal process bearing seta av on telefemur II. This attribute is apparently not described in other laelapid mites. Also, males of L. lignicola are similar to those of some European species of Cosmolaelaps in having a distinct masticatory ridge on the fixed digit of chelicera. The ecological preference for decaying wood microhabitats, where L. lignicola is closely associated with Lasius emarginatus (Olivier) (Hymenoptera Formicidae), also suggests a close affinity with Cosmolaelaps species. Consequently, this species is provisionally placed in Cosmolaelaps and the new combination C. lignicolus (G. & R. Canestrini, 1882) comb. nov. is proposed.